New opportunities in the treatment of mixed bacterial infections in women - V. N. Kuzmin (Лечащий Врач, 2022)
Mixed bacterial infections cause reproductive disorders, in the form of inflammatory diseases of the pelvic organs, tubal infertility and ectopic pregnancy. A promising macrolide drug is spiramycin. Spiramycin is a highly effective drug in the treatment of uncomplicated and complicated urinary tract infections caused by chlamydia and ureaplasma, which can be used as monotherapy and as part of a complex treatment of sexually transmitted infections. Of particular importance is the proven safety of spiramycin therapy for infections at any stage of pregnancy. Therefore, the main principles of rational antibacterial therapy are the determination of the microflora that caused the infectious process, the assessment of the impact of the antibiotic on the fetus and the ways of its elimination, as well as the early start of therapy, the assessment of its effectiveness in the first 48 hours, the control of side effects. In infectious-inflammatory diseases, especially mixed bacterial infections, the use of the combined drug (ornidazole 500 mg and ciprofloxacin 500 mg) is considered justified. The results of the study of the vaginal microbiota showed that its flora is almost completely represented by anaerobic microorganisms. The appearance on the pharmaceutical market of secnidazole, a new generation antimicrobial agent, made it possible to implement a new approach to the treatment of bacterial vaginosis. Secnidazole, unlike clindamycin, does not have activity against beneficial lactobacilli and one can expect a minimal effect on the predominant Lactobacillus component of the normal healthy microflora. In the presence of intestinal dysbacteriosis, the infectious process acquires a protracted course, which requires repeated courses of antibiotic therapy and exacerbates dysbacteriosis. After the end of taking antibiotics, it is advisable to correct the state of the microbiocenosis of the vagina. Thus, the tactics of an obstetrician-gynecologist, based on the use of a set of measures for the treatment and prevention of infections, can reduce the incidence of complications in women of reproductive age.